Evaluation of the rest-intake index in a food and nutrition unit of a city of Maranhão (Research, Society and Development, 2020)
The present study had the objective of evaluating the rest-intake index in a food and nutrition unit of a municipality of Maranhão. This is a cross-sectional study, with a quantitative approach, carried out at a University Restaurant (UK) in a municipality of Maranhão. It is observed that of the 49 commensals, 18 presented% of wastage up to 3% which is the maximum allowed to be considered a good meal, 16 students had a percentage between 3.1 and 10% and 15 students had values higher than 10%. It was concluded that the percentage of rest-ingestion in the UAN exceeded the values recommended in the literature making it necessary to carry out actions with the commensals for knowledge of their food preferences, in addition to campaigns related to waste for awareness, as well as periodic training with the employees aiming at minimizing waste and improving the quality of services.